Simulation of hybrid push/pull production system for cost reduction and resource optimization in sustainable automotive manufacturing - Harrtyan Muhammad; Ratih Dyah Kusumastuti (Sustainable Urban Development and Environmental Impact Journal, 2025)
​​​Background: The rapid development of the automotive industry requires an efficient production system to minimize costs and optimize resources. PT XYZ, an automotive component manufacturer, previously relied on a push production system based on demand forecasts. However, discrepancies between forecasted and actual demand led to excess inventory and increased storage costs. To address this issue, a hybrid push/pull production system was introduced, aiming to balance inventory levels while maintaining production efficiency. Methods: This study employs a discrete event simulation method using Arena software to analyze the impact of implementing a hybrid push/pull production system at PT XYZ. The research utilizes company data from October 2016 to compare the efficiency of different production scenarios. Findings:  Findings indicate that adopting a hybrid push/pull production system significantly reduces inventory costs while preventing backorders. The system modifies the upstream process by transitioning from forecast-based production to a pull system that aligns with actual demand. Meanwhile, the push system remains in use for raw materials and semi-finished components to ensure production continuity. Additionally, worker and machine utilization decreased, allowing the company to reallocate resources for other product lines, thereby enhancing production capacity. Conclusion: The study concludes that implementing a hybrid push/pull production system provides PT XYZ with a competitive advantage by reducing operational costs without compromising demand fulfillment. However, this system requires careful inventory tracking and employee adaptation. In the long run, reduced storage costs lead to substantial savings. Novelty/Originality of this article: The novelty of this research lies in its application of hybrid push/pull production to an SME automotive manufacturer in Indonesia, demonstrating its effectiveness in reducing costs and improving resource utilization.